Chapter 10: Gender equality in organizations: the dynamics of space (Edward Elgar Publishing, 2022)
Gender equality goals have proven to be difficult for organizations to achieve. Management scholars attribute gender equality's intractability to decoupling: Organizations adopt structures, policies and programs that fail to deliver their intended outcomes. We present a conceptual framework that draws on recent developments in institutional logics, acknowledging that stakeholders are diverse and care about different things at different times. Our framework portrays organizational activities as operating across three distinct metaphorical spaces (physical, mental, and social). Physical space describes the organization's formal structures, policies and programs. Mental space is the organizational members' shared meaning about the organization's identity (including what management researchers have called diversity climate). Social space is the external stakeholders' shared perception of the organization's identity (including what management researchers have called diversity reputation). Management literature has historically emphasized activities originating in the physical space. We use case examples to illustrate how organizations might avoid decoupling by simultaneously attending to all three spaces. The framework identifies opportunities for organizations to harness cross-space dynamics, embrace divergent institutional logics, and enable progress toward gender equality.